Determination of Phosphorous Fixation Capacity on Alluvium, Sandstone and Shale Soils of Akwa Ibom State, Nigeria - F. O, Umoh; O. A, Essien; C. J, Ijah; A. E, Sunday (International Journal of Sustainable Agricultural Research, 2021)
The study was aimed to determine the fixation capacity of phosphorous from three parent materials (Alluvium, Shale and Sandstone) in Akwa Ibom State. A composite soil samples were collected from three representative locations. A treatment solution containing 0, 20, 40 and 80mgl-1 of P prepared from KH2PO4 were added to 20g of soil samples in a cups and incubated for 1, 7, 30 and 60 days. The design was 3 x 4 factorial experiment (3 soil types and 4 rates of P) were fitted into Completely Randomized Design (CRD) with three replications. At a set day, the exchangeable and water soluble P were extracted with Bray P – 1 extractant and P not extracted was considered fixed in the soils. The results revealed that the soils were fertile and moderately acidic and than the amount of phosphorous fixed in shale and alluvium soils, decrease with length of incubation and a significant higher fixation were observed in day 1 (60.6 mgkg-1 shale and 50.6mgkg-1 in alluvium). The amount observed in sandstone increased with the length of incubation and a significant amount fixed was observed in 30 days (54.4mgkg-1). The study also revealed that the concentration of P fixed increased with increasing rates of P added in all the soils. Base on the inherent fertility of the soils, the use of crop rotation and organic manure is recommended to maintain its fertility for high productivity.